Proceedings of the 5th Conference on Computing Frontiers 2008
DOI: 10.1145/1366230.1366276
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating advanced mri reconstructions on gpus

Abstract: core CPU is thirteen times slower. Furthermore, relative to the true image, the error exhibited by the advanced reconstruction is only 12%, while conventional reconstruction techniques incur error of 42%. In short, the acceleration afforded by the GPU greatly increases the appeal of the advanced reconstruction for clinical MRI applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 26 publications
(35 reference statements)
0
30
0
Order By: Relevance
“…It was shown that, using 200 iterations, the processing times were around 2 h for this dataset. As most of the postprocessing is dominated by the 3D gridding algorithm, we believe it is possible to speed up each iteration using more efficient algorithms, or even graphical processing units (24).…”
Section: Figmentioning
confidence: 99%
“…It was shown that, using 200 iterations, the processing times were around 2 h for this dataset. As most of the postprocessing is dominated by the 3D gridding algorithm, we believe it is possible to speed up each iteration using more efficient algorithms, or even graphical processing units (24).…”
Section: Figmentioning
confidence: 99%
“…Since the advent of general purpose usage of GPUs, medical computing [6], [7], energy sciences [8], image/video processing [9], [10], finance [11] and many other problems in different areas have been ported on to GPU platforms in order to gain performance. In this paper we propose an implementation of Lempel-Ziv-Storer-Szymanski(LZSS) lossless data compression on NVIDIA GPUs (CULZSS).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, dedicated hardware solutions have been developed in the past [1,2] in order to process images in real-time. However, with the overwhelming development of graphics processing units (GPUs) in the last decade also graphics cards became a serious alternative and were consequently deployed as accelerators for image processing [3].…”
Section: Introduction and Related Workmentioning
confidence: 99%